Compressive strength behavior of treated marine clay using ordinary portland cement and blast furnace slag - Kuan Siew Fung, 1989-, author 645392; Ramli Nazir, supervisor 611019; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik))